Mad and divine - "Kakar, Sudhir" (New Delhi, 2008)
Sudhir Kakar, India$1 (Bs foremost psychoanalyst has for long tried to infuse the pre-eminently Western discipline of psychoanalysis with ideas and views from the East in both his practice and his best-selling books. In Mad and Divine, he takes on the separat s
Keywords: Spiritualism